Influentiality of Social Media Influencers on Purchase Intension of Consumers: A Regional Perspective - Sahaf, Muskaan Fayaz; Nazir, Arif (International Journal of Media and Communication Research, 2024)
Businesses are starting to use social media influencers (SMIs) as a new way to persuade their target audience to buy something. This is because consumer stratification is growing quickly. Social media's pervasiveness, as well as its broad reach and frequency, have made it a thriving advertising strategy, outperforming more traditional forms of advertising. In this study, the researchers focus on divulging the need to employ social media influencers in marketing services and their impact on consumers. The research attempts to trace the effectiveness of social media influencing in comparison to traditional forms of advertising and to promulgate the pros and cons of the emerging advertising strategy through social media influencers. The researchers' findings were based on a mixed method of research that included quantitative and qualitative data collected through surveys and interviews. The researchers discovered that despite influencers have a strong influence on consumer purchasing decisions, the new advertising trend through Social Media Influencers is on the rise in Kashmir Valley. However, the overall findings reveal that influencer marketing holds the upper hand in the market when it comes to influencing target groups effectively.